Antibody therapy of multiple sclerosis - Coles, Alasdair; Compston, Alastair (Henry Stewart Talks, 2007)
The story of multiple sclerosis, Symptoms, Pathogenesis, Pathological heterogeneity, Axonal degeneration, Current treatments, Interferons and glatiramer, Monoclonal antibody treatment of multiple sclerosis, Daclizumab, Natalizumab, The story of Campath-1H, The effect of Campath-1H on disability depends upon the stage of the disease, Graves' disease, Immune thrombocytopenia, Future treatment of multiple sclerosis